Modeling and controller design of a hybrid stepper motor - Abdul Majid, Mohd. Zaini (2013)
Hybrid stepping motors are being used extensively over a wide range of application especially for precise positioning. This is due to their advantages of having higher efficiency, maintain very high resolution due to the small step angle and other advantages over other types of stepping motor. Therefore this project takes for granted to model their transient performance over various situations. This project is mainly based on modeling and controller design of two phase hybrid stepping motor. The presented model and controller is able to perform the transient performance. The model is developed in Matlab-Simulink with conventional PID controller and Fuzzy Logic controller. The conventional PID controller and Fuzzy logic controller used to reduce the settling time and overshoot. The model described the motor current and voltages as well as performing the speed and track position responses for the rotor during each excitation. Using this model, it is capable of performing the simulation of hybrid stepping motor with various parameters. The simulations results are presented with a detail explanation on each part of the study conducted. The results show that hybrid stepping motor can be used for precise positioning especially when small step angle are required.